2013
DOI: 10.5511/plantbiotechnology.13.0904a
|View full text |Cite
|
Sign up to set email alerts
|

Advances in tomato research in the post-genome era

Abstract: The tomato (Solanum lycopersicum) draft genome, along with a draft of the wild relative, Solanum pimpinellifolium, were released in 2012, almost a decade after the International Tomato Genome project was initiated. Tomato is an important domesticated crop species, as well as a model organism for many aspects of plant biology such as fleshy fruit development, ripening, disease resistance, plant architecture, and compound leaf development. For these reasons, there has been a substantial effort for producing a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 121 publications
1
14
0
Order By: Relevance
“…Bioinformatics studies based on the tomato sequence, which serves as a reference genome for other Solanaceae species, have demonstrated that the tomato genome may serve as a true reference genome for closely related Solanaceae and may enable studies of orthologous genes and gene families both within tomato and among more divergent plants (Menda et al, 2013). Systematic analysis of the phylogeny and expression of these genes during reproductive developmental stages in tomato will be helpful for mining candidate genes for subsequent detailed characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics studies based on the tomato sequence, which serves as a reference genome for other Solanaceae species, have demonstrated that the tomato genome may serve as a true reference genome for closely related Solanaceae and may enable studies of orthologous genes and gene families both within tomato and among more divergent plants (Menda et al, 2013). Systematic analysis of the phylogeny and expression of these genes during reproductive developmental stages in tomato will be helpful for mining candidate genes for subsequent detailed characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the largest number of SNPs were observed in chromosome 12, followed by chromosome 1 and 10 ( Figure 1). The existence of unanchored scaffolds (Chr00) and the large [2]. It also highlights the importance of identifying new intraspecific SNPs in the tested tomato breeding lines.…”
Section: Discussionmentioning
confidence: 97%
“…For example, molecular markers (SNP and InDels) were developed based on whole-genome re-sequencing of two tomato lines (Caimanta and LA0722) and using those markers in a segregating population; eventually, BS disease resistance lines were developed [59]. Menda et al [60] have reviewed the various genomics resources that can be used in tomato improvement.…”
Section: Exploiting Tomato Genomic Resourcesmentioning
confidence: 99%